2012
DOI: 10.1016/j.jvs.2011.10.124
|View full text |Cite
|
Sign up to set email alerts
|

Endothelium-dependent nitric oxide and hyperpolarization-mediated venous relaxation pathways in rat inferior vena cava

Abstract: Introduction The vascular endothelium plays a major role in the control of arterial tone; however, its role in venous tissues is less clear. The purpose of this study was to determine the role of endothelium in the control of venous function, and the relaxation pathways involved. Methods Circular segments of inferior vena cava (IVC) from male Sprague-Dawley rats were suspended between two wires and isometric contraction to phenylephrine (Phe, 10−5M) and 96 mM KCl was measured. Acetylcholine (Ach, 10−10 to 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 55 publications
(97 reference statements)
1
9
0
Order By: Relevance
“…Cells lacking KCNN3 are less responsive to the vasodilator acetylcholine and shear stress on the vascular wall [7]. Little is known on the role of SK channels in venous vasoregulation [8].…”
Section: Exome Sequencingmentioning
confidence: 99%
“…Cells lacking KCNN3 are less responsive to the vasodilator acetylcholine and shear stress on the vascular wall [7]. Little is known on the role of SK channels in venous vasoregulation [8].…”
Section: Exome Sequencingmentioning
confidence: 99%
“…Endothelium‐dependent relaxation caused by the activation of muscarinic receptors has been demonstrated not only in arteries but also in veins obtained from different species, including equine digital vein (Elliot et al., ), horse dorsal penile vein (Martínez et al., ), rabbit jugular vein (Itoh, Maekawa, & Shibayama, ), and rat inferior vena cava (Raffetto, Yu, Reslan, Xia, & Khalil, ). However, the venous endothelium produces and releases less amount of vasodilators than the arterial counterpart (Eguchi & Katusic, ).…”
Section: Discussionmentioning
confidence: 99%
“…Acetylcholine endothelium‐dependent relaxation can include an EDH component in some veins, such as the jugular and the superior cava vein (Itoh et al., ; Raffetto et al., ). Since, the L‐NAME/indomethacin combination abolished the endothelium‐dependent relaxation to acetylcholine, it is unlikely the presence of an EDH‐mediated relaxation component in the isolated bovine digital vein.…”
Section: Discussionmentioning
confidence: 99%
“…In rats, Rees et al (1989) [114], found that blocking the formation of NO with the inhibitor L-NMMA resulted in an immediate rise in blood pressure and that the subsequent administration of the L-arginine substrate reversed this effect. NO also plays a role in the endothelium-dependent venous relaxation [115].…”
Section: Methodsmentioning
confidence: 99%